AKTIVITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2013 – 2015) - Angga Setyaji, 13.05.51.0211 (Students' Journal of Economic and Management, 2017)
This study axamined the effect of liquidity ratio, activity ratio, solvability ratio and firm size to profitability at manufacturing business in Indonesian stock axchange period 2013-2015. Population in this research ic company of manufacture sector with enlist in Indonesian stock exchange. Sample research with criterion wich have been determained to be obtained by counted 71 manufacturing company which public`s company in indonesian stock exchange, with data pooled method or panel data during year 2013-2015, so that the amount of sample ( n )= 71 x 3 = 213, while use by method is multiple linier regression. The test result variable liquidity significant positif to profitability, aktivity significant positif to profitability, solvability significant negatif to profitability and firm size significant positif to profitability. Keyword : profitability, liquidity, activity, solvability and firm size.